Síntese, caracterização de cocristais e sais-cocristais de ingredientes farmacêuticos ativos - Delling, Felix Nicolai (2016)
Using techniques/procedures of green chemistry, solid state grinding, solvent drop grinding and solvent drop grinding with heating, twenty compounds were synthesized. Eleven compounds of dropropizine (antitussive): two co-crystals and nine co-crystal salts, nine compounds of carbamazepine (anticonvulsant and mood stabilizer) were synthesized: eigth channel compounds and a possible co-crystal. The sulfamethoxazole (bactericidal) showed not to be a good choice as no new compounds could be synthesized in the reaction conditions used for all experiments, only its hemihydrate could be obtained. The compounds were characterized by powder X-ray diffraction, infrared spectroscopy, differential scanning calorimetry, mass spectrometry and single crystal X-ray diffraction methods. Using infrared spectroscopy it was possible to identify four characteristic vibrational modes for the salts, i.e. two vibrational modes of the COO- species (~1540 and ~1358 cm-1) and two of the N+–H species (~1385 and ~1258 cm-1). For the co-crystals the characteristic stretch of the carboxylic acids, at ~1700cm-1, did not disappear. The crystal, molecular and packing structures of two compounds, i.e. of the sulfamethoxazole hemihydrate and of the salt of dropropizine with 4-hydroxybenzoic acid, were determined by single crystal X-ray diffraction. Mechanisms were proposed for the solid state grinding and solvent drop grinding with heating reactions. Finally, a proton transfer mechanism was proposed for the solid state grinding and solvent drop grinding with heating to synthesize a salt.